The Effect Of Polyphenols On Hemostasis System Disorders In Rats With Experimental Diabetes (Texas Journal of Multidisciplinary Studies, 2025)
Hemostasis disorders in patients with diabetes mellitus include the activation of natural coagulation mechanisms, suppression of fibrinolytic activity, and platelet dysfunction. In this regard, investigating this issue and searching for new pharmaceutical agents that can prevent the progression of type 2 diabetes mellitus and the development of its complications in the hemostasis system is a highly relevant problem. Our studies have revealed that a polyphenol extracted from Pistacia vera and an extract from Isatis tinctoria L. possess antidiabetic and antithrombotic activity. It was demonstrated that these polyphenols improve glycemic control in rats with experimentally induced type 2 diabetes and also reduce the incidence of thrombotic complications.